2021
DOI: 10.1186/s12885-021-07866-w
|View full text |Cite
|
Sign up to set email alerts
|

ERK3 is transcriptionally upregulated by ∆Np63α and mediates the role of ∆Np63α in suppressing cell migration in non-melanoma skin cancers

Abstract: Background p63, a member of the p53 gene family, is an important regulator for epithelial tissue growth and development. ∆Np63α is the main isoform of p63 and highly expressed in Non-melanoma skin cancer (NMSC). Extracellular signal-regulated kinase 3 (ERK3) is an atypical mitogen-activated protein kinase (MAPK) whose biochemical features and cellular regulation are distinct from those of conventional MAPKs such as ERK1/2. While ERK3 has been shown to be upregulated in lung cancers and head and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We have recently demonstrated that ERK3 directly contributed to AP-1/c-Jun activation, IL-8 production and chemotaxis 52 . Emerging studies have further shown that ERK3 functions in a context- and tissue-specific manner in controlling tumourigenesis and metastasis 50, 51, 53, 56, 81, 88, 89 . Mice expressing a catalytically inactive ERK3 mutant survive to adulthood and are fertile, but the kinase activity of ERK3 is necessary for optimal postnatal growth.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that ERK3 directly contributed to AP-1/c-Jun activation, IL-8 production and chemotaxis 52 . Emerging studies have further shown that ERK3 functions in a context- and tissue-specific manner in controlling tumourigenesis and metastasis 50, 51, 53, 56, 81, 88, 89 . Mice expressing a catalytically inactive ERK3 mutant survive to adulthood and are fertile, but the kinase activity of ERK3 is necessary for optimal postnatal growth.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK6 is shown to be a key factor for organogenesis, cancer cell growth and invasiveness. MAPK6 overexpression has been detected in numerous human cancers, including squamous cell lung carcinoma, oral squamous cell carcinoma, gastric cancer, breast cancer and melanoma 53 . DNA microarray studies have produced inconsistent information about the regulation of MAPK6 expression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ΔNp63α is the predominant and physiologically significant isoform of p63 in epithelial tissues (Alshammari et al, 2021). Recently, ΔNp63α has been proposed as another possible PSF since it can induce a pEMT by activating Slug (SNAIL2) as well as inhibiting ZEB via miR-205 (Dang et al, 2016).…”
Section: Phenotypic Stability Factors (Pfs)mentioning
confidence: 99%